FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PERUBAHAN SIKLUS MENSTRUASI PADA MAHASISWI DHARMA HUSADA PEKANBARU TAHUN 2019 - Sari, Endah Purwani (Jurnal Martenity and Neonatal, 2019)
Menstrual cycle is the amount between the first menstrual period and the next menstrual period. Data from basic health research (RISKESDAS, 2013) shows that most 68% of women in Indonesia aged 10-59 years report regular menstruation and 13.7% experience irregular menstrual cycle problems in the past year. The purpose of this study was to determine the factors associated with changes in menstrual cycles for female students of akper Dharma husada pekanbaru in 2019.This type of research is to use analytic quantitative research design. The population in the study were all the scholarship students of Dharma Husada Pekanbaru akper in 2019 who experienced irregular menstrual cycles, univariate and bivariate data analysis techniques, and data collection methods using questionnaires with a sample of 40 respondents.Based on the results of univariate and bivariate studies, it was shown that irregular menstrual cycles in the Dharma Husada akper scholarship students of Pekanbaru and based on the first age factor of menstruation, ie from 40 respondents experienced normal menache 22 respondents (50.0%), abnormal as many as 18 respondents (45, 0%). based on IAF factors namely active 16 respondents (40.0%) and less active as many as 24 respondents (60.0%). And based on BMI factors that are not obese as many as 37 respondents (92.5%), obesity 3 respondents (7.5%). And based on the menstrual cycle, namely the smooth menstrual cycle of 15 respondents (37.5%) and not normal as many as 25 respondents (62.5%). The chi-square test found that there was a relationship between menarche and the menstrual cycle P = 0.03 (Pvalue 0.03 <0.005), and the relationship between physical activity and the menstrual cycle P = 0.04 (p value 0.04 <0.005), and not correlation between body mass index and menstrual cycle P = 0.27 (Pvalue, 0.27> 0.005).So the researcher can conclude that there is a relationship between menarche and physical activity with the menstrual cycle. It is hoped that the akbid akper Dharma husada pekanbaru students will be able to do physical activities or exercise regularly.